OPTIMIZATION THE BEST TEACHER SELECTION BASED ON THE COMPOSITE PERFORMANCE INDEX (CPI) AT SMKN 1 SETIA JANJI - Andri Nata; Andrew Ramadhani; Fauriatun Helmiah (JURNAL TEKNISI, 2025)
Abstract: Â Teachers are a key element in the success of education, but the selection of the best teachers at SMKN 1 Setia Janji has so far been subjective. This can lead to less than optimal results and does not reflect teacher performance comprehensively. This study aims to optimize the selection of the best teachers by implementing the Composite Performance Index (CPI) method as an assessment system based on a composite performance index. This method allows the integration of various assessment indicators, such as academic performance, discipline, innovation in teaching, and student responses to teacher teaching methods. This study uses a quantitative approach with data collection through documents, surveys, and interviews. Furthermore, the data is analyzed using the CPI calculation to produce a performance index for each teacher. The results of the study indicate that the CPI method is able to provide more objective, transparent, and accountable results in determining the best teachers. By eliminating subjectivity in the assessment, this method can also increase teacher motivation and strengthen a work culture based on achievement in schools. From the evaluation results, it was found that the CPI not only increases accuracy in the selection of the best teachers, but also provides a fairer and more comprehensive assessment standard. The findings of this study contribute to the development of a more effective teacher performance evaluation system, especially in the SMKN 1 Setia Janji environment.Keyword: best teacher selection; composite performance index (CPI); decision support system.Â Abstrak: Guru merupakan elemen kunci dalam keberhasilan pendidikan, namun pemilihan guru terbaik di SMKN 1 Setia Janji selama ini masih bersifat subjektif. Hal ini dapat menyebabkan hasil yang kurang optimal dan tidak mencerminkan kinerja guru secara komprehensif. Penelitian ini bertujuan untuk mengoptimalkan pemilihan guru terbaik dengan menerapkan metode Composite Performance Index (CPI) sebagai sistem penilaian berbasis indeks kinerja komposit. Metode ini memungkinkan integrasi berbagai indikator penilaian, seperti kinerja akademik, kedisiplinan, inovasi dalam pengajaran, serta tanggapan siswa terhadap metode pengajaran guru. Penelitian ini menggunakan pendekatan kuantitatif dengan pengumpulan data melalui dokumen, survei, dan wawancara. Selanjutnya, data dianalisis menggunakan perhitungan CPI untuk menghasilkan indeks kinerja setiap guru. Hasil penelitian menunjukkan bahwa metode CPI mampu memberikan hasil yang lebih objektif, transparan, dan akuntabel dalam menentukan guru terbaik. Dengan menghilangkan subjektivitas dalam penilaian, metode ini juga dapat meningkatkan motivasi guru dan memperkuat budaya kerja berbasis prestasi di sekolah. Dari hasil evaluasi, ditemukan bahwa CPI tidak hanya meningkatkan akurasi dalam seleksi guru terbaik, tetapi juga memberikan standar penilaian yang lebih adil dan menyeluruh. Temuan penelitian ini berkontribusi dalam pengembangan sistem evaluasi kinerja guru yang lebih efektif, khususnya di lingkungan SMKN 1 Setia JanjiKata kunci: pemilihan guru terbaik; composite performance index (CPI); sistem pendukung keputusan.